Typology of Almaty’s public open spaces by spatial planning - Glaudinova, Mekhribanu; Anuar, Aznamkhan; Abdullah, Alias (2025)
This study examines the typology of public open spaces (POS) in Almaty based on their spatial and planning structures. Urban open spaces play a key role in fostering social interaction, improving environmental quality, and shaping the aesthetics of the urban environment. Despite their significance, systematic studies addressing the structural diversity of POS in Almaty remain limited. The primary objective of this research is to classify POS according to their planning structure and to identify patterns that may inform urban design and policymaking. The study employs a mixed-methods approach that includes field surveys, spatial analysis, and classification techniques. Data were collected for 137 public open spaces in Almaty, including parks, squares, green areas, and other recreational zones. Each site was analyzed in terms of layout configuration, connectivity, and accessibility. Observational mapping and GIS-based analysis were used to establish structural categories. The results reveal the main typologies of POS in Almaty and provide detailed descriptions of each type. Quantitative assessment identifies the distribution of these typologies across the city and their relationship to functional diversity and user engagement. In conclusion, the findings of this study provide a foundation for further research on how planning typologies of public open spaces influence user behavior and the quality of the urban environment. The resulting typological models can be applied to evidence-based urban design, the planning of new public spaces, and the evaluation of existing POS. Moreover, the study contributes to the advancement of urban planning theory and practical approaches to creating functionally and socially sustainable urban environments.